THE PROBLEM OF THE BREST UNION IN HISTORICAL LITERATURE OF XIX AND XX CENTURIES - Shved, R. (Pedagogy of Higher and Secondary Education, 2002)
The article shows the role of the Brest union in the formation of national consciousness o f the Ukrainian nobility and Cossacks.